Cross-lingual C*ST*RD: English Access to Hindi Information - Leuski, Anton; Lin, Chin-Yew; Zhou, Liang; Germann, Ulrich; Och, Franz Josef; Hovy, Eduard (ACM Transactions on Asian Language Information Processing, 2003)
We present C*ST*RD, a cross-language information delivery system that supports cross-language information retrieval, information space visualization and navigation, machine translation, and text summarization of single documents and clusters of documents. C*ST*RD was assembled and trained within 1 month, in the context of DARPA’s Surprise Language Exercise, that selected as source a heretofore unstudied language, Hindi. Given the brief time, we could not create deep Hindi capabilities for all the modules, but instead experimented with combining shallow Hindi capabilities, or even English-only modules, into one integrated system. Various possible conﬁgurations, with different tradeoffs in processing speed and ease of use, enable the rapid deployment of C*ST*RD to new languages under various conditions.